Reattachment of crosslinked poly(ethylene oxide) via chain interpenetration and reentanglement induced by a simple wetting process. (27th October 2017) - Lee, Hoik; Ryu, Jungju; Kim, Jeong Rae; Kim, Myungwoong; Kim, Ick Soo; Sohn, Daewon
Abstract: We demonstrate the reattachment of two chemically-crosslinked poly(ethylene oxide) (PEO) matrix samples prepared with the γ-ray irradiation method by a simple wetting process with a good solvent. The fractured polymer samples can be attached through chain diffusion, interpenetration into a crosslinked network, and intermixing/reentanglement. Reattached samples exhibit similar macro/microstructure and mechanical properties to those of pristine samples. This effective recovery process without any additional reactive chemicals or external stimuli highlights the importance of extending the use of simple, but fundamental, dynamic behaviors of polymer chains to obtain the desired properties as well as offering a unique and useful route toward effective healable materials. Graphical abstract: Highlights: Two crosslinked PEO samples prepared by the γ-ray irradiation method were reattached by a simple wetting process. Wetting with water allowed PEO chains to diffuse across fractured surfaces to become intermixed and reentangled. Reattached samples exhibited similar macro/microstructure and mechanical properties to those of pristine samples. This effective recovery process highlights the use of effective healable materials.